The relationship between income level and road traffic deaths: an empirical analysis for 22 OECD countries - Yuksel Bayraktar; Serdar Aydin; Mehmet Firat Olgun; Ayfer Ozyilmaz; Metin Toprak (BMC Public Health)
Abstract Background The increase in transportation and travel demands leads to the development of social welfare, and on the other hand, it may adversely affect socio-economic indicators such as death, injury, air pollution and budget deficit. Every day, thousands of people are killed, injured, or disabled due to road accidents around the world. The high cost of fatal and non-fatal road accidents to national economies is important in terms of policies to be implemented. This study aims to examine the relationship between road accidents and income levels in 22 OECD countries. Methods Poisson Regression, Negative Binomial, and Quantile Regression Fixed Effect were used in models estimation. In addition, the convergence of traffic accident deaths for 34 OECD countries was investigated. Fractional frequency unit root test with structural break was used for convergence analysis. Results The findings of the study show that there is an inverted U-shaped nonlinear relationship between road accident deaths and per capita income. In addition, while the increase in health expenditures reduces the number of deaths due to traffic accidents, the increase in alcohol consumption increases these deaths. The results obtained from the convergence analysis indicates that 21 OECD countries converge to the OECD average, but 13 countries do not converge. Conclusions Infrastructure investments for road safety such as traffic lights, curves, wide highways should be effectively implemented by the public. Pedestrians or drivers who put road safety at risk should be given deterrent penalties when necessary. In addition, public awareness should be increased regarding traffic rules and life safety. Trial registration Not applicable.